Violations of Conversational Maxims in Investigative Interviews: Revisiting the Indonesian Cyanide Coffee Murder Case - Aulia Addinillah Arum; Nadia Khumairo Ma’shumah (k@ta: A Biannual Publication on the Study of Language and Literature, 2025)
This study advocates the role of forensic linguistics in detecting lies during investigative interviews with suspects and witnesses, with a focus on the case of Jessica Kumala Wongso, who was convicted and sentenced to 20 years’ imprisonment for the cyanide poisoning of Wayan Mirna Salihin. Drawing on the cooperative principle and conversational maxims theories, this study examines the deceptive language used by suspects. The dataset was manually collected through purposive sampling from court transcripts and in-depth news interviews to ensure both relevance and analytical rigor. The analysis indicates that deceptive communication involves deliberate strategic violations of Grice’s conversational maxims, specifically those relating to the maxims of quality and quantity. These findings are consistent with McCornack et al.’s Information Manipulation Theory 2, which posits that lies arise through the covert manipulation of informational components within conversational exchanges. This study underscores the importance of these maxims as a systematic analytical framework for detecting deception and also demonstrates their potential to enhance the accuracy of evidence evaluation in criminal investigations.